Effect of bovine milk fermented with Lactobacillus rhamnosus L8020 on periodontal disease in individuals with intellectual disability: a randomized clinical trial - ODA Yuki; Chiaki FURUTANI; Yuika MIZOTA; Atsuko WAKITA; Sumiyo MIMURA; Takuya KIHARA; Masaru OHARA; Yoshiyuki OKADA; Mitsugi OKADA; Hiroki NIKAWA
Abstract Studies on the oral health of individuals with intellectual disability (ID) have identified problems that include a high prevalence of periodontal disease. The use of probiotics to treat periodontal disease has been the focus of considerable research, and bovine milk fermented with Lactobacillus rhamnosus L8020 (L8020 yogurt) has been shown to reduce the oral prevalence of four periodontal pathogens. Objective The aim of this randomized, double-blind, placebo-controlled trial was to compare the effects of L8020 yogurt (test group) with those of placebo yogurt (placebo group) on the papillary-marginal-attached (PMA) index, gingival index (GI), and probing depth (PD) in 23 individuals with ID. Methodology All patients were required to consume the allocated yogurt after breakfast for 90 days. PMA index and GI scores as well as PDs were assessed before the start of yogurt consumption (baseline), after 45 and 90 days of consumption, and 30 days after the cessation of consumption. Student's t-test, Mann-Whitney U test or Fisher's exact test was used for inter-group comparisons, and the mixed effect model of repeated measurements was used for data analysis. Results The decrease in PMA index score was significantly greater in the test group than in the placebo group (p<0.001). The GI score also decreased during the study, with a tendency for greater decrease in the test group. Furthermore, decreases in PD between baseline, 45 and 90 days tended to be greater in the test group than in the placebo group. Conclusion These results suggest that regular consumption of bovine milk fermented with L. rhamnosus L8020 can lower the risk of periodontal disease in individuals with ID.